X-linked ichthyosis in a patient with congenital hypothyroidism. - Guarnieri, M.; Stagi, S.; Manoni, C.; Battini, M.L.; Massi, D.; Galluzzi, F.; Salti, R. (European Journal of Pediatric Dermatology, 2004)
Thyroid hormones play a major role in brain metabolism, growth and development and the serious consequences of thyroid hormone deprivation have been well documented. In congenital hypothyroidism the prevalence of congenital malformations (8-15%), particularly involving the nervous system and heart, is higher than in the general population (1-2%). The structure of the skin may be affected to varying degrees. Increasing evidence shows that thyroid hormones exert an important and interesting action on the skin. We described a newborn with a clinical spectrum of congenital hypothyroidism and X-linked ichthyosis. To the best of our knowledge, it is the first report regarding this association. We could hypothesize that a steroid sulfatase enzyme deficiency, which is commonly found in X-linked ichthyosis, plays a role in the thyroid metabolism. Ichthyosis must be evaluated in patients with congenital hypothyroidism. Thyroid function may be evaluated in patients with X-linked ichthyosis in order to diagnose possible hypothyroidism.